RECONSTRUCTION OF DISABILITY-FRIENDLY NATIONAL FIQH: A PARADIGM TRANSFORMATION FROM RUKHSHAH TO ÁZIMAH - Syamsuri Syamsuri (JURNAL HAKAM, 2026)
This article examines the reconstruction of disability-friendly fiqh kebangsaan (national Islamic jurisprudence) through a paradigmatic shift from the rukhsah (legal concession) approach to ‘azīmah (normative obligation) within the context of the Indonesian nation-state. Prevailing discourses on disability in classical Islamic jurisprudence predominantly frame persons with disabilities as recipients of individual dispensations, resulting in a charity-based approach that inadequately addresses systemic discrimination embedded in public policy, employment, and social institutions. Employing a normative-critical analysis of classical fiqh texts, legal maxims, national regulations, and international human rights instruments—particularly the Convention on the Rights of Persons with Disabilities (CRPD)—this study argues that the rukhsah paradigm must be transformed into an ‘azīmah-oriented framework that positions the state as an active duty-bearer in guaranteeing disability rights. The findings reveal three major insights: first, legal maxims such as al-mashaqqah tajlib al-taysīr and al-ḍarar yuzāl should not be narrowly interpreted as individual exemptions but rather as normative mandates for inclusive public policies; second, classical Islamic political jurisprudence has implicitly articulated state responsibility toward vulnerable groups, although this dimension has not been systematically developed in contemporary fiqh discourse; and third, the integration of fiqh kebangsaan with principles of social justice and international human rights law produces a jurisprudential model oriented toward empowerment rather than benevolence. This article concludes that the ‘azīmah approach is more contextually relevant to Indonesia and aligns with both maqāṣid al-sharī‘ah and substantive justice. Policy recommendations include strengthening derivative legislation of the Disability Law, allocating inclusive public budgets, and enhancing the institutional authority of the National Disability Commission.